2006
DOI: 10.1080/01485010500397964
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Y Chromosome Microdeletions in Tunisian Infertile Men

Abstract: The aim of this study was to establish the prevalence of Y chromosomal microdeletions in infertile Tunisian men. Three groups of infertile men, 65 normospermic, 53 oligozoospermic and 45 azoospermic, were tested for Yq microdeletions detection by multiplex polymerase chain reaction (PCR) using specific Y chromosome AZF regions tagged site markers (STS). One group of 13 healthy men was used as the control group. Six STS were tested (2 in each AZF region). The general prevalence of AZF microdeletions was 16%; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
1
5
0
1
Order By: Relevance
“…In this study, least number of total Y chromosome deletions was observed in AZFa (8.33%) and AZFb (33%) region whereas maximum deletion was seen in AZFc (41.6%) region. This is in agreement with the earlier studies which showed that the incidence of deletion in the AZFc region was high compared with the AZFa and AZFb regions [8][9][10][11].…”
Section: Pcr Analysis For Y Chromosome Microdeletionssupporting
confidence: 93%
“…In this study, least number of total Y chromosome deletions was observed in AZFa (8.33%) and AZFb (33%) region whereas maximum deletion was seen in AZFc (41.6%) region. This is in agreement with the earlier studies which showed that the incidence of deletion in the AZFc region was high compared with the AZFa and AZFb regions [8][9][10][11].…”
Section: Pcr Analysis For Y Chromosome Microdeletionssupporting
confidence: 93%
“…We found that 102 of 210 (48%) patients had noncytogenetically detectable microdeletions. However, following the European Academy of Andrology (EAA) guidelines we found that only 16% had Y chromosome microdeletions (HadjKacem et al, 2006). The position and extent of the deletions are shown schematically in Figure 1a.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, there are wide variations in the reported frequency of microdeletion in Tunisian population. Using the Y chromosome microdeletion in infertile Tunisian men 6 STSs markers, Hadj-Kacem et al [19] have reported an overall of 16% of Y chromosome microdeletions in 163 infertile Tunisian men with normal karyotype subdivided into 3 groups: azoospermic, oligozoospermic (less than 20 × 10 6 spz/mL), and normozoospermic men (more than 20 × 10 6 spz/mL). With the same STSs markers, two studies performed by Ghorbel et al have detected a lower frequency in azoospermic and oligozoospermic groups: 1.3% [6] and 2.7% [20], but chromosomal abnormalities in these reports were included in the first study and unspecified in the latter one ( [22].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the methods applied for the Yq microdeletion screening in Tunisian studies might account for varying deletion frequencies. The choice and number of STS markers differed widely, ranging from 6[6,19,20] to 20 STS[21] despite the fact that Simoni et al showed that the detection rate did not depend on the number and choice of markers used…”
mentioning
confidence: 99%